Psychological Interventions in Anxiety Treatment in People with Breast Cancer: a Meta-Analysis - Zelaya-Rivas, Susana María (2020)
Objective. This study aims to estimate the effect size of psychological interventions for anxiety treatmentin people diagnosed with breast cancer. Method. A systematic review of online databases (Dialnet, Ebsco, Latindex, PubMed, ScienceDirect, Wiley, SAGE, Scielo, and Google Scholar) was carried out, through which experimental and quasi-experimental articles relevant to the analysis were retrieved. From the selected articles, data were extracted regarding the participants, the treatments used, and pre and post test data from the groups for analysis. Results. Seventeen articles that met the inclusion criteria were used in the analysis. The overall effect size of the interventions was determined (g = -.459). Likewise, bias and continuous moderating variables analyses were performed.